2018
DOI: 10.2147/dddt.s163157
|View full text |Cite
|
Sign up to set email alerts
|

Lobaplatin inhibits breast cancer progression, cell proliferation while induces cell apoptosis by downregulating MTDH expression

Abstract: ObjectiveLobaplatin shows antitumor activity against a wide range of tumors, including metastatic breast cancer (BCa). The overexpression of metadherin (MTDH) is associated with poor prognosis of BCa patients. This study was designed to investigate the effect of lobaplatin on MCF-7 cell proliferation and its association with MTDH expression.Patients and methodsClinical treatment for BCa using lobaplatin, in combination with other general chemotherapy drugs, was administered to 32 BCa patients. The safety, effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
(79 reference statements)
0
8
0
Order By: Relevance
“…SCD1 inhibition has been reported before to inactivate the AKT signaling, seen in higher rates of cell apoptosis in human lung adenocarcinoma ( 72 ). FBXW7 promotes apoptosis of BC cells through the ubiquitination and proteolysis of the oncoprotein metadherin (MTDH) ( 73 ), whose expression is related to various pathways, for example, the AKT signaling pathway ( 74 ). Furthermore, the inhibition of MTDH gives rise to apoptosis of cancer cells probably due to the downregulation of the AKT signaling ( 75 , 76 ).…”
Section: Fbxw7 and The Hallmarks Of Cancermentioning
confidence: 99%
“…SCD1 inhibition has been reported before to inactivate the AKT signaling, seen in higher rates of cell apoptosis in human lung adenocarcinoma ( 72 ). FBXW7 promotes apoptosis of BC cells through the ubiquitination and proteolysis of the oncoprotein metadherin (MTDH) ( 73 ), whose expression is related to various pathways, for example, the AKT signaling pathway ( 74 ). Furthermore, the inhibition of MTDH gives rise to apoptosis of cancer cells probably due to the downregulation of the AKT signaling ( 75 , 76 ).…”
Section: Fbxw7 and The Hallmarks Of Cancermentioning
confidence: 99%
“…The mechanism of lobaplatin’s anti-neoplastic effect may be attributed to JNK (c-Jun N-terminal) phosphorylation, ROS activation (reactive oxygen species), cell pyroptosis, and apoptosis. 32 , 33 However, the specific mechanism by which lobaplatin facilitates TNBC elimination warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that efficient and tumor-specific knockdown of the MTDH gene attenuates paclitaxel resistance of breast cancer cells both in vivo and in vitro 9 . Down-regulation of MTDH expression can inhibit breast cancer progression and cell proliferation, and induce cell apoptosis in breast cancer 28 . Silencing the expression of MTDH increases the radiation sensitivity of SKOV3 OC cells and reduces their proliferation and metastasis 10 .…”
Section: Discussionmentioning
confidence: 99%